Teach Aquaculture Curriculum: Anatomy of a Fish - Amber L. Garr; Cortney L. Ohs; Craig S. Kasper; R. Leroy Creswell; Frank A. Chapman; Brian E. Myers; Elisa J. Livengood; Carlos V. Martinez (EDIS)
FA173, a 5-page activity by Amber L. Garr, Cortney L. Ohs, Craig S. Kasper, R. Leroy Creswell, Frank A. Chapman, Brian E. Myers, Elisa J. Livengood, and Carlos V. Martinez, is activity 1 of the Teach Aquaculture Curriculum. In this activity for grades 5-12, students categorize types of fish, describe the basic biology of fish species, and identify the primary functions of anatomical features common to aquaculture. Includes student performance standards. Published by the UF School of Forest Resources and Conservation, Program in Fisheries and Aquatic Sciences, July 2010.